PERFORMANCE COMPARISON OF DOUBLE-SWITCH CUK CONVERTER AND CUK CONVERTER - Akbar, Alif Aulia; Hasanah, Rini Nur; Nurwati, Tri (Jurnal Mahasiswa TEUB, 2024)
The conversion of high voltage with continuous input and output is a crucial requirement for current applications such as electric vehicles and renewable energy. In this research, a converter is proposed based on the Cuk converter by modifying the components into two switches, three inductors, three diodes, and four capacitors. The duty cycle and pulse signals on both switches are the same. The circuit analysis process is carried out using the continuous conduction mode method, assuming eachcomponent is in an ideal state. The analysis is conducted in two modes: when the switch is on and when the switch is off. Simulation and circuit analysis are shown to convert an input voltage of 12 volts to 156 volts on the output side. Simulations are conducted to analyze the input voltage, input current, output voltage, output current, voltage on the capacitor, current on the inductor, and then compare the changes in duty cycle to the output voltage, changes in duty cycle to efficiency, changes in duty cycle to the voltage stress on the switch and diode, and voltage stress on the switch relative to voltage gain. The results of these comparisons indicate that this converter can provide higher efficiency and a wider voltage gain capability with lower voltage stress value. Keywords: Cuk Converter, Efficiency, Simulation, Voltage Stress